Narrating an urban adventure: Montessori pre-school and day-care centre, Kingspark Zoo redevelopment - De Kock, Riana (University of the Free State, 2014)
This thesis addresses the rejuvenation of a large part of the inner city. The design is motivated by the circumstances of the current urban landscape which fails to provide adequate play spaces for children. Karsten (2005 cited in Beneker, Sanders, Tani, Taylor, 2010: online) recognizes the disappearance of children playing freely in public spaces and that children only appear in the urban landscape under the strict supervision of adults. It is therefore of vital importance to incorporate this as a requirement into the brief for future urban planning schemes, and will also be addressed in this thesis. For the purpose of this thesis it is assumed that the existing premises of Bloemfontein Kingspark Zoo are proposed for low-scale lowdensity development while preserving this area as a green lung in the inner city. This inner-city development programme comprises a supervised park, coffee shop, private offices and preschool and day-care centre and is driven by the hypothetical Bloemfontein Development Agency. As part of the zoo development masterplan the pre-school and day-care centre will provide a safe and supervised space within the city for children. Bringing children to the city should mediate adults with children and generate a landscape with new characteristics by means of architecture and urban planning. The park-like landscape of the existing zoo in contrast to the ‘concrete jungle’ renders a dramatic playscape where children, protected from harm, can allow their imaginations to roam free. From children’s natural ability to translate ‘things’ of the everyday world into the obstacle and creature of an epic adventure, this thesis finds its conceptual basis. The proposed project will analogously attempt an architectural translation of the innate narrative qualities of children. As a conceptual basis the thesis will investigate this playscape and imaginative adventures as navigational tools for the design Spatial representation of Fairy Tales will be explored and will form part of the design rationale with the intention of generating exhilarating spatial experiences.
Keywords: Dissertation (M.Arch. (Architecture))--University of the Free State, 2014; Inner city rejuvenation; Bloemfontein, South Africa; Children